Pengaruh Ukuran Perusahaan, Profitabilitas, Dan Likuiditas Terhadap Nilai Perusahaan Pada Sektor Transportasi Dan Logistik Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2023 - Alsha Fianingsih Putri; Sigit Puji Winarko; Faisol Faisol (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This study aims to analyze the effect of firm size, profitability, and liquidity on firm value in the transportation and logistics sector listed on the Indonesia Stock Exchange during 2020–2023. This study uses a quantitative approach with secondary data obtained from annual financial reports. The sample was selected through purposive sampling and resulted in 11 companies over 4 years, totaling 44 observations. Panel data regression analysis was performed using STATA-14. The results show that partially, firm size and liquidity do not significantly affect firm value, while profitability has a significant positive effect. Simultaneously, all three variables significantly affect firm value. This finding implies that profitability is a main concern for investors when assessing firm value.